Ergogenic, anti-diabetic and antioxidant attributes of selected Malaysian herbs: characterisation of flavonoids and correlation of functional activities - Sallehuddin, N. A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2020)
In the present work, aqueous ethanolic (60% ethanol) extracts from selected Malaysian herbs including Murraya koenigii L. Spreng, Lawsonia inermis L., Cosmos caudatus Kunth, Piper betle L., and P. sarmentosum Roxb. were evaluated for their ergogenic, anti-diabetic and antioxidant potentials. Results showed that the analysed herbs had ergogenic property and were able to activate 5'AMP-activated protein kinase (AMPK) in a concentration dependant manner. The highest AMPK activation was exhibited by M. koenigii extract which showed no significant (p > 0.05) difference with green tea (positive control). For anti-diabetic potential, the highest α-glucosidase inhibition was exhibited by M. koenigii extract with IC50 of 43.35 ± 7.5 μg/mL, which was higher than acarbose (positive control). The determinations of free radical scavenging activity and total phenolics content (TPC) indicated that the analysed herbs had good antioxidant activity. However, C. caudatus extract showed superior antioxidant activity with IC50 against free radical and TPC of 21.12 ± 3.20 μg/mL and 221.61 ± 7.49 mg GAE/g, respectively. RP-HPLC analysis established the presence of flavonoids in the herbs wherein L. inermis contained the highest flavonoid (catechin, epicatechin, naringin and rutin) content (668.87 mg/kg of extract). Correlations between the analyses were conducted, and revealed incoherent trends. Overall, M. koenigii was noted to be the most potent herb for enhancement of AMPK activity and α-glucosidase inhibition but exhibited moderate antioxidant activity. These results revealed that the selected herbs could be potential sources of natural ergogenic and anti-diabetic/antioxidant agents due to their rich profile of phenolics. Further analysis in vivo should be carried out to further elucidate the mechanism of actions of these herbs as ergogenic aids and anti-diabetic/antioxidant agents.